Representation of Women's Beauty in the Korean Drama "True Beauty" : A Peircean Semiotics Analysis - Setiawan, Shafira Nandya; Rohanda; Gia Ramadhan (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study thoroughly examines the representation of female beauty in the Korean drama True Beauty using Charles Sanders Peirce's semiotic approach. The widespread phenomenon of the Korean Wave (Hallyu) in Indonesia has significantly impacted the construction of beauty standards, often creating social pressure, especially for teenagers and young women. True Beauty, which tells the story of Lim Ju Kyung's struggle to meet appearance expectations, serves as an interesting object for analysis. Utilizing Peirce's triadic framework (representamen, object, and interpretant), this study identifies how visual and verbal signs within the drama construct meaning. The analysis reveals that representamens, such as Ju Kyung's with her bare face, the act of self-makeup, the rejection of her bare face, and social acceptance, collectively refer to the object patriarchal Korean beauty standards demanding fair skin, a high nose bridge, and a slender physique. The resulting interpretants vary on one hand, viewers may perceive beauty as a condition for social acceptance and a source of anxiety, but on the other hand, the drama also presents alternative interpretants highlighting the importance of self- acceptance and resistance to narrow beauty standards. This study concludes that True Beauty not only reproduces dominant beauty norms but also creates space for critique and encourages critical media literacy regarding more inclusive representations of gender and body.